Screening general practice patients for migraine without aura: construction and validation of the Balkan Migraine Screening Questionnaire (BMSQ) - Aziz Šukalo; Elma Merdžanović; Alma Alic; Muamera Vrabac-Mujčinagić; Esad Alibašić; Slobodan M. Janković (Medicinski glasnik, 2019)
Aim: To develop and validate a screening questionnaire for migraine without aura with sufficient diagnostic accuracy to be used in primary care settings. Methods: The study was designed as cross-sectional, multicentric, diagnostic accuracy trial of new questionnaire for screening patients who visit general practitioners, with an aim to reveal migraine without aura. The instrument was constructed for the purpose of this study, and validated on the sample of 429 primary care outpatients. The gold standard of diagnosing migraine without aura was clinical estimate by a neurologist based on the International Classification of Headache Disorders 3rd edition (ICHD-III) criteria. Diagnostic accuracy of the instrument was tested through construction of the Receiver Operator Curve. Results: The Balkan Migraine Screening Questionnaire (BMSQ) instrument showed good diagnostic accuracy (sensitivity 83.4% and specificity 79.9%) for migraine without aura, with significant screening yield among previously undiagnosed patients of 75.9%. The study also confirmed a high percentage of patients with hidden migraine without aura (MWA) (52.9%) revealed by the BMSQ and the ICHD-III criteria that would otherwise remain undiagnosed. Conclusion: The BMSQ is a valid and reliable clinical instrument for revealing migraine without aura, which could be easily selfadministered by patients. It has high screening yield, discovering majority of patients with previously undiagnosed migraine without aura, whose definite diagnosis should later on be confirmed by the attending physicians using the ICHD-III criteria.
Keywords: diagnosis; migraine without aura; questionnaire design; screening migraine disorders; validation studies